The Growing Mpox Infections by Clade I Variant in African Countries Is a Public Health Emergency of International Concern: A Narrative Review - Taslima Jamal Urmi; Md. Rabiul Islam (Health Science Reports)
ABSTRACT Background and Aim In 2022, the monkeypox (mpox) outbreak was declared a public health emergency of international concern. The emergence of a new strain in the Democratic Republic of the Congo and its identification with neighboring countries led to the declaration of a public health emergency in 2024. The objective is to focus on the recent outbreak that led to its declaration as a Public Health Emergency of International Concern, assess the significant global public health threat posed by the newly identified class, and explore effective strategies to address this situation. Methods The present review searched information from databases (PubMed and Scopus), WHO, and the European Centre for Disease Prevention and Control. The search methods followed database‐specific criteria. Key terms included mpox, prevalence, public health emergency, treatment, new variant, prevention, and strategy. We reviewed and extracted information from the relevant literature. Results Mpox has been endemic in the Democratic Republic of the Congo for over a decade, with a consistent annual rise in reported cases. In August 2024, at least 13 African countries have confirmed 2,863 cases and 517 fatalities. The recent emergence and transmission of a new strain, which appears to be predominantly spreading through sexual networks, along with its identification in neighboring countries, raises significant concerns for public health. Conclusion The emergence of the new clade of mpox represents a critical public health challenge that necessitates immediate and coordinated global response efforts. By addressing the current outbreak comprehensively, we can mitigate its impact and safeguard public health across affected regions.